PROTOYPE HEAT EXCHANGER TYPE SHELL AND TUBE DITINJAU DARI VARIASI JARAK BAFFLE DAN LAJU ALIR MASSA UDARA PANAS - Marawijaya, Gede; ., Tahdid; Trisnaliani, Lety; Purna, Candra (Politeknik Negeri Sriwijaya, 2019)
The use of heat exchangers in the industrial world is very widely used both to reduce or where the temperature is in accordance with the needs of various products. The development of technology and science causes heat exchangers to experience various transformations. In its development, the heat exchanger undergoes a form transformation which aims to improve efficiency in accordance with its work function. The form of heat exchanger that is often used is shell and tube. The process in the heat exchanger type of shell and tube is by flowing the hot fluid in the tube and cold fluid in the shell with the type of cross flow flow. In the heat exchange process of shell and tube type heat exchangers, there are several things that need to be considered to obtain the effectiveness of maximum heat transfer, including the type of fluid, flow rate, temperature, heat transfer rate, pressure drop, shell dimension and tube (pipe), baffle distance, pitch distance, tube arrangement, and material type. The influence of various factors can be seen from the effectiveness and efficiency produced. Effectiveness of the highest heat transfer at variations in baffle distance of 15 cm is 82,13% and the highest efficiency at mass flow rate is 45 kg / hour which is 85,27%.